Pengaruh Kompetensi, Pengakuan dan Kepuasan Kerja Terhadap Keterlibatan Kerja Pegawai PDAM Tirta Moedal Kota Semarang - Irfan Rizki Nurhidayat; Mohammad Fauzan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze and explain the influence of (1) competence on work engagement, (2) recognition of work involvement and (3) job satisfaction on work involvement in PDAM Tirta Moedal Semarang City. This research is a type of explanatory research. The research sample was 98 people. The data collection technique uses a questionnaire distributed through google forms. Data analysis uses multiple linear regression with the help of SPSS software. The results of the research findings showed that (1) competence had a positive effect on work engagement, (2) recognition had a positive effect on work engagement, (3) job satisfaction had a positive effect on work involvement of PDAM Tirta Moedal Semarang City.